A prospective Study of Ultrasound Screening for Molar Pregnancies in Missed Miscarriages in Eastern Region of Afghanistan - Rahimi, Suhaila; Hashimi, Sayed Azizullah; Wiyar, Sayed Arif (International Journal For Research In Applied And Natural Science, 2021)
Introduction Miscarriage is the natural death of an embryo or fetus before it is able to survive independently. The most common symptom of a miscarriage is vaginal bleeding. About 80% of miscarriage occur in the first 12 weeks of pregnancy. Objective: The aim of this study was to prospectively evaluate the role of ultrasound examination in screening for molar changes in women diagnosed with a first-trimester miscarriage. In addition to examine the relationship between ultra- sound and histological features in the screening for molar changes in missed miscarriage. Methods: A prospective cohort study was conducted on all missed miscarriages, with features suspicious of molar pregnancy, on transvaginal ultrasound and/or on histological examination in Nangarhar University Teaching Hospital over a 2-year period. All cases of molar pregnancy diagnosed histologically were examined and cross-referenced with cases diagnosed on ultrasound and with the supplementary report from the regional referral center. When available, maternal serum β-human chorionic gonadotropin (hCG) levels were recorded. Results: seventy-one cases of suspected molar pregnancy were referred to the regional center for further histological opinion and follow-up, and nine cases were subsequently excluded from the final analysis because of the diagnosis of hydropic abortion (HA). In 45 cases a molar pregnancy was suspected at the initial scan. Of these, 35 (77.7%) were confirmed on histology, resulting in a 56% detection rate using ultrasound alone. In 20 cases hCG results were available, of which twelve were greater than two multiples of the median. Conclusions: The diagnosis of both complete (CHM) and partial (PHM) hydatid form moles in first-trimester miscarriages is difficult. hCG is significantly higher in both CHM and PHM and, in conjunction with transvaginal ultrasound, could provide the screening test required to enable clinicians to counsel women more confidently towards non-surgical methods of management of their miscarriage, where histopathological examination is not available.